Surface quality and cutting power requirement after edge milling of thermally modified meranti (Shorea spp.) wood. (May 2020) - Kamboj, Gourav; Gašparík, Miroslav; Gaff, Milan; Kačík, František; Sethy, Anil Kumar; Corleto, Roberto; Razaei, Fatemeh; Ditommaso, Gianluca; Sikora, Adam; Kaplan, Lukáš; Kubš, Jiří; Das, Sumanta; et al.
Abstract: The objective of this study was to investigate the influence of thermal modification on surface quality and cutting power of machines for processing of meranti wood. Meranti wood samples were exposed to thermal modification with temperature of 160, 180 and 210 °C. Surface roughness and waviness were evaluated after edge milling with cutting speed of 20, 30 and 40 m/s, rake angle of 15, 20 and 25° and feed rate of 4, 8, and 11 m/min. The energy consumption during milling was calculated from the average cutting power. Cutting parameters had a significant effect on surface quality. Thermally-modified wood exhibited a reduction in the cutting power requirement with increasing modification temperature. The lowest cutting power of 283 W was obtained in wood thermally modified at 210 °C and the highest value of 793 W was observed in unmodified wood. The optimum surface quality and energy consumption were obtained with a cutting speed of 20 m/s, rake angle of 25°, feed rate of 4 m/min and modification temperature of 210 °C. Highlights: Thermal modification (TM) had a significant effect on the chemical composition of meranti wood. Hemicellulose proportion reduced; lignin and cellulose proportion increased with increase in modification temperature. Thermal modification improved the surface quality of meranti wood; better surface quality was obtained at 210 °C. Cutting power during milling decreased significantly with increase in modification temperature. Optimum surface and energy use were obtained at 20 m/s cutting speed, 25° rake angle, 4 m/min feed speed and TM at 210 °C.